Real practices in the reality of humanity Confirm that the genealogy is not correct - Jaber Jassim, Ahmed (Al-Adab Journal, 2020)
The beginning of human creation as it is in religions proves that the Almighty Creator began the human creation with one mother, father and one, and no other, They are Eve and Adam, and Eve gave birth with the power of the Creator, a female twin and a male in every pregnancy, so Adam married the first female abdomen, the second female, And the second belly male marries the first female belly until the Cain rebellion in this way, so what happened was chaos and sexual porn in which all men became for all women and all women for all men so the newborn did not know his father because of that and the mother was raising her baby, It is driven by the instinct of motherhood and the role of the mother at this stage is the prominent role, so it is called the role of motherhood and supports the stage of sexual disorder Mamors later from habits, to name a few.The multiplicity of men that the one woman and the newborn call, as the woman raises him and is attributed to her because his father cannot be known among them because of their multiplicity.